Health Sciences: Advancing Healthcare through Interdisciplinary Approaches and Innovation - Sharma, Priya; Mishra, Ravinesh; Sharma, Bhartendu; Kumari, Archana; Modgil, Swati (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Health sciences encompass a diverse range of disciplines that combine insights from medicine, biology, public health, nursing, pharmacology, and other related fields to enhance human health. The primary purpose is to improve the understanding of human health as it develops alongside disease progression together with treatment effectiveness for both personal and community populations. Healthcare systems now redirect their focus towards population health management while expanding medical care from conventional settings to community-based health strategies to deliver affordable quality services. Changes in the healthcare environment require professionals to master evidence-based methods while effectively using technology along with teamwork between different professionals. Healthcare has undergone revolutionary changes through medical research which has delivered breakthrough treatments through "Gene editing, immunotherapy, nanotechnology, and mRNA vaccines." Public health programs use three prevention levels including primary and secondary and tertiary healthcare measures in addition to risk factor reduction and wellness support. Different countries across the globe operate different healthcare models which include Beveridge Bismarck National Health Insurance systems for financing their health services delivery methods. The health sciences industry continues to deal with various hurdles that include data privacy issues as well as mental health stigma and cybersecurity concerns and AI integration difficulties alongside regulatory complications. The healthcare industry needs ongoing innovative approaches and collective efforts to establish fair healthcare structures that are both efficient and eco-friendly. Health sciences with an emphasis on accessible and efficient compassionate care play a fundamental role in delivering better patient results and better healthcare practices for worldwide health equity.